Influencia de las competencias digitales en el desempeño docente Facultad de Ciencias de la Educación y Humanidades – UNAP Iquitos 2023 - Huamán Núñez, Hulior (2025)
The main objective of this research was to explain the influence of digital competencies on teaching performance in the Faculty of Education Sciences and Humanities of the UNAP, Iquitos, during the year 2023. The study was developed under a quantitative approach, with a type of explanatory research, correlational level and non-experimental correlational-causal design. The population consisted of 145 teachers, from which a sample of 105 participants was selected by probability sampling with proportional and simple random assignment. For data collection, two structured questionnaires were applied, one on digital competencies and the other on teacher performance in the use of ICT, both previously validated. The results revealed that 56.19% of the teachers presented an average level of digital competencies and 57.14% showed an intermediate level in their teaching performance, which showed considerable room for improvement. The multiple regression analysis indicated that the digital competencies -instrumental, didactic-methodological and cognitive- together explained 93.4% of the variability in teaching performance (R² = 0.934), with a statistically significant influence (p < 0.001). The didactic-methodological dimension had the greatest impact individually (B = 0.571; p < 0.001). It was concluded that the integral development of digital competencies, beyond the technical domain, is key to enhance the quality of teaching performance in digitized university contexts.